Nursing vigilance in preventing catheter fragment migration: a dual case report of peripheral venous catheter fractures in pediatric practice - Pu, Lingling; Zhang, Youcheng; Chen, Weibing; Meng, Hongyan (Frontiers in Pediatrics, 2025)
BackgroundIndwelling venous catheters, including peripheral intravenous catheters (PIVCs), are vital in pediatric care for delivering medications and fluids. However, catheter fractures, though rare (incidence 0%–2.1%), pose serious risks such as pulmonary embolism or cardiac arrhythmias if fragments migrate. While central venous catheter fractures are well-documented, PIVC fractures are underreported despite their widespread use.Case presentationThis report details two pediatric cases of PIVC fractures. In the first, a 1-day-old female neonate experienced a fractured left axillary catheter. Nursing staff promptly applied compression and immobilization, enabling successful surgical retrieval of a 3.5 cm fragment within 6 h, with no complications. In the second, a 1-year-old male infant had a right temporal vein catheter fracture, unrecognized for 6 days due to initial oversight, resulting in localized inflammation. CT angiography and ultrasound confirmed fragment locations, guiding surgical removal of a 1.5 cm fragment.DiscussionThese cases highlight the rarity of PIVC fractures and the pivotal role of nursing vigilance in early detection—marked by signs like resistance during flushing or swelling. Timely interventions, such as compression and immobilization, prevent fragment migration and improve outcomes, as seen in the neonate, contrasting with the delayed case. Risk factors include excessive manipulation, improper site preparation (e.g., unshaved hair), and patient agitation. Preventive measures—thorough hair removal, secure fixation, daily inspections, and agitation management—are critical. Nursing education, standardized protocols, and vascular access teams enhance safety.ConclusionPIVC fractures in pediatrics, though uncommon, demand nursing alertness and swift action. This series underscores the need for preventive strategies and training to optimize patient safety and outcomes.